2018
DOI: 10.17576/jsm-2018-4704-10
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Mutagenic Activity of Herbal Tea Prepared from Cosmos caudatus Leaves at Different Maturity Stages

Abstract: Different maturity stages of Cosmos caudatus leaves have been used to prepare herbal tea were investigated for their effect on antioxidant activity and mutagenic activity. The analyses carried out were total phenolic content (TPC), total flavonoid content (TFC), ferric reducing antioxidant power (FRAP), 2-2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, β-carotene bleaching assay, oxygen radical absorbance capacity (ORAC) and Ames Salmonella mutagenicity. The results demonstrated that, C. caudatus herbal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…When the IC50 value of the sample was lower, the antioxidant activity was higher. 23 The IC50 value of the present study showed that ALLURA TM has a high antioxidant capacity as compared to the previous data from Dian-Nashiela et al 22 who reported that C. caudatus herbal tea extracted from the leaves had an lC50 value of 1055 µg/mL.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…When the IC50 value of the sample was lower, the antioxidant activity was higher. 23 The IC50 value of the present study showed that ALLURA TM has a high antioxidant capacity as compared to the previous data from Dian-Nashiela et al 22 who reported that C. caudatus herbal tea extracted from the leaves had an lC50 value of 1055 µg/mL.…”
Section: Discussionsupporting
confidence: 55%
“…Meanwhile, TFC value of the present study was high as compared to the TFC value of herbal tea from a commercial brand, 17.92 mg QE/mL. 22 DPPH is usually expressed as IC50, the amount of antioxidant necessary for decreasing the initial concentration of DPPH by 50%. When the IC50 value of the sample was lower, the antioxidant activity was higher.…”
Section: Discussionmentioning
confidence: 58%
“…The maturity of leaf may affect its antioxidant level, which gave different results of antioxidant level of berry crops' leaf according to the leaf maturity [7]. A research also proved that maturation of Cosmos caudatus leaf decreases its antioxidant capacity [8]. Hence, in this study, the leaf of P. sarmentosum is chosen to be further investigated for the effects of its leaf maturity on its antioxidant level.…”
Section: Introductionmentioning
confidence: 99%